PROGRAM MODELS FOR INTERACTIVE DESIGN OF FAULT-TOLERANT SYSTEM WITH MIXED STRUCTURAL REDUNDANCY TAKING ACCOUNT MAINTENANCE SERVICE STRATEGIES - Mandziy, Bohdan; Volochiy, Bohdan; Ozirkovskyy, Leonid (International Journal of Computing, 2014)
The problem of development of program models of the fault-tolerant system with the mixed structural redundancy is solved. For designing of program models an advanced technology of analytical modeling of the systems is used. This technology takes into account all features of structure and behavior of the system under the action of refusals and two variants of realization of maintenance service strategy. It provides possibility of multiple analysis at the small expenses of time. The results of researches of the fault-tolerant system, which illustrate possibilities of decision of tasks of reliability analysis and reliability synthesis, are resulted in the article.